Juvenile hormones and juvenoids : modeling biological effects and environmental fate - Devillers, J. 1956- (QSAR in environmental and health sciences., 2013)
"Series Introduction The correlation between the toxicity of molecules and their physicochemical properties can be traced to the nineteenth century. Indeed, in a French thesis entitled Action de l'alcool amylique sur l'organisme (Action of amyl alcohol on the body), which was presented by A. Cros before the Faculty of Medicine at the University of Strasbourg in 1863, an empirical relationship was made between the toxicity of alcohols, their number of carbon atoms, as well as their solubility. In 1875, Dujardin-Beaumetz and Audigier the first to stress the mathematical character of the relationship between the toxicity of alcohols and their chain length and molecular weight. In 1899, Hans Horst Meyer and Fritz Baum, at the University of Marburg, showed that narcosis or hypnotic activity was in fact linked to the affinity of substances to water and lipid sites within the organism. At the same time at the University of Zurich, Ernest Overton came to the same conclusion providing the foundation of the lipoid theory of narcosis. The next important step was made in the 1930s by Lazarev in St. Petersburg, who first demonstrated that different physiological and toxicological effects of molecules were correlated with their oil- water partition coefficient through formal mathematical equations in the following form: log C = a logPoil/water + b. Thus, the quantitative structure-activity relationship (QSAR) discipline was born. Its foundations were definitively fixed in the early 1960s by the seminal works contributed by C. Hansch and T. Fujita"--